Exploring differential engagement with mathematics support from an engineering student focus. (23rd December 2021) - Gokhool, Farhana; Lawson, Duncan; Hodds, Mark; Aslam, Farzana
Abstract: This paper explores the differential engagement of engineering students with mathematics support at Coventry University. Mathematics support is an additional help in mathematics that is offered to all students at the University, and engagement with such support is voluntary. Attendance records show that, whilst many students do engage with mathematics support, there are others who do not, even though their results indicate that they might benefit from so doing. Previous studies of engagement with mathematics support have either treated the student cohort as a whole or explored the effect of a single demographic factor such as age or gender. This paper investigates the effect of a range of demographic factors on the engagement of engineering students with mathematics support.